2003
DOI: 10.1002/chin.200336117
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydroquinoline‐Based Selective Estrogen Receptor Modulators (SERMs).

Abstract: Quinoline derivatives Quinoline derivatives R 0410Tetrahydroquinoline-Based Selective Estrogen Receptor Modulators (SERMs).-The design and synthesis of a series of substituted tetrahydroquinolines such as (VI) and (X) starting from commercially available N-oxide (I), their binding affinities to estrogen receptors and antagonism of estradiol in MCF-7 breast adenocarcinoma cells are reported. Compound (X) is the most potent inhibitor of MCF-7 proliferation identified in this series. -(WALLACE*, O. B.; LAUWERS, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 1 publication
2
12
0
Order By: Relevance
“…Consequently, the selectivity ratio was also reduced, dropping to 2.6 for 89, while 84 showed an almost 10-fold selectivity for ERb over ERa. 96 Pfizer has described the preparation of several 1,2,3,4-tetrahydroisoquinolines, among which some ERb-selective ligands were found. 97 This is the case for compounds 90 and 91 ( Fig.…”
Section: Naphthalenes Quinolines Tetrahydroquinolines Tetrahydroismentioning
confidence: 99%
“…Consequently, the selectivity ratio was also reduced, dropping to 2.6 for 89, while 84 showed an almost 10-fold selectivity for ERb over ERa. 96 Pfizer has described the preparation of several 1,2,3,4-tetrahydroisoquinolines, among which some ERb-selective ligands were found. 97 This is the case for compounds 90 and 91 ( Fig.…”
Section: Naphthalenes Quinolines Tetrahydroquinolines Tetrahydroismentioning
confidence: 99%
“…The synthesis of β-lactam antibiotics has occupied an important place in the field of medicinal and research pharmaceutical. The antibiotic activity of Azetidine-2-ones (β-lactam) possessing antiviral, antifungal activities, antithrombotic and cholesterol inhibition [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Many pharmaceutical agents and different natural products with significant biological activity are built on the (tetrahydro)quinoline scaffolds (Katritzky et al , 1996; Kouznetsov et al , 1998). A large number of reports showed that these compounds display a wide spectrum of biological activities, including antimalarial activity (Bendale et al , 2007), estrogenic receptor (Wallace et al , 2003; Chen, et al , 2007), anti-inflammatory behavior (Calhoun et al 1995), among others.…”
Section: Introductionmentioning
confidence: 99%